2015
DOI: 10.1063/1.4913574
|View full text |Cite
|
Sign up to set email alerts
|

Eggs and milk: Spinning spheres partially immersed in a liquid bath

Abstract: When a hard-boiled egg spins through a pool of milk on the kitchen counter, the milk rises up the sides of the egg and droplets are ejected. This phenomenon occurs when any partially submerged object whose radius increases upward from the fluid surface (e.g., spheres, inverted cones, and rings) spins in a liquid bath. The fluid ejects from the surface near the maximum radius in one of three ejection modes: jets, sheets, or sheet breakup. Additionally, a surprisingly large flow rate is induced by the spinning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…(1)-( 3) in their study of the rotary atomization for Newtonian liquids (a more recent study has been performed by Truscott and coworkers [24]). In their studies they found that by increasing either the rotation rate of the cup, or the flow rate of the supplied fluid, three separate regimes 033601-5 emerge and they represented these regimes in a dimensionless parameter space corresponding to the values of two closely related dimensionless product groups 1 = ω ρD 3 /σ = √ 8We and…”
Section: Dimensionless Operating Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…(1)-( 3) in their study of the rotary atomization for Newtonian liquids (a more recent study has been performed by Truscott and coworkers [24]). In their studies they found that by increasing either the rotation rate of the cup, or the flow rate of the supplied fluid, three separate regimes 033601-5 emerge and they represented these regimes in a dimensionless parameter space corresponding to the values of two closely related dimensionless product groups 1 = ω ρD 3 /σ = √ 8We and…”
Section: Dimensionless Operating Mapmentioning
confidence: 99%
“…By varying the flow rate and the centripetal acceleration, researchers have observed several different regimes of fragmentation for Newtonian liquids [20][21][22]. There have been several attempts at quantifying the transition criteria separating these different regimes [20,21,23,24]. Also, several semiempirical correlations have been suggested for the variation in average droplet size with rotation rate, feed rate and fluid properties [11,21,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the rise of a hard-boiled egg from horizontal to vertical when spun sufficiently rapidly on a table allows to discuss concepts of solids mechanics 8,9 . Also, an egg spinning through a pool of milk on the kitchen counter and inducing milk rise and droplet ejection constitutes a nice exama) Electronic mail: yann.bertho@universite-paris-saclay.fr ple of fluid mechanics and capillary phenomenon 10 . Among the possible experiments that can be realized with an egg, some of them involve the complex fluids contained inside the eggshell.…”
Section: Introductionmentioning
confidence: 99%